Trends and Impacts in Conflict Settings : The Socio-economic Impact of Conflict-driven Displacement in the ESCWA Region (United Nations, 2009)
Thirty-six per cent of displaced persons in the world are to be found in the ESCWA region, where conflict and war-driven displacement have resulted in 7.6 million refugees and 7.2 million internally displaced. This study, which is the first to appear in the Trends and Impacts in Conflict Settings series, is an attempt to analyse displacement as a conflict-driven regional trend and its socio-economic implications for ESCWA member countries. The study also aims at raising awareness on the phenomenon of displacement as a regional issue and the need for coordinated regional strategies to address its impact on the displaced population, the host countries and the region as a whole. It offers recommendations to ESCWA member countries and the international community on the formulation of regional policies and programmes to support displaced communities and proposals for further research that would inform the development of policies aimed at mitigating the impact of conflict-driven displacement in the region.